Cognitive function in early psychosis patients from a lower middle-income country. (2nd January 2018) - Husain, Muhammed Omair; Chaudhry, Imran B.; Thomasson, Rachel; Kiran, Tayyeba; Bassett, Paul; Husain, Muhammad I.; Naeem, Farooq; Husain, Nusrat
Abstract: Objectives: To establish evidence of cognitive changes in early psychosis (EP) patients compared to healthy controls (HC) in Pakistan. Methods: Fifty-one participants with EP were recruited from psychiatric units in Karachi and Rawalpindi, Pakistan and matched with 51 HC. Neurocognitive domains were assessed using standardised neuropsychological tests [the Stroop test, block design, Matrix Reasoning, picture completion, object assembly, oral fluency, memory for design, Coughlan learning task (verbal and visual)]. Results: EP patients had higher scores than controls for both Stroop tests (T1: EP = 122 HC = 65, p  <.001; T2: EP = 190 HC = 153, p  = .007) and memory for design test (EP = 10 HC = 3, p  = .005). EP group had lower values for block design (EP = 4, HC = 11, p  = .01), category fluency (EP = 18.9, HC = 26.1, p  < .001), Coughlan verbal tasks (EP = 36.4 NC = 51.5, p  < .001), matrix reasoning (EP = 4 NC = 10, p  < .001), picture completion (EP = 4 NC = 6, p  = .003) and object assembly (EP = 10.7, HC = 15.5, p  = .002). There were limited significant associations between cognitive performance and PANSS scores. Conclusions: Reduced cognitive performance was found across multiple domains in Pakistani EP patients, which suggests that impaired cognitive performance is homogenous in patients with schizophrenia, regardless of ethnicity.